The Birth of Solidarity - Kemp-Welch, A. author. aut Link
IX, 261 p.
Keywords: This book describes the origins and birth of Solidarity in 1980, its rebirth in 1989, and the formation of a Solidarity government. This second edition is now enlarged to include fresh documentation of the 1980 strike, a further mmoire on the experts' role 'behind the scenes', and an entirely new chapter 'From Gdansk to Government'. Taken together, the analysis and documentation provide a permanent record of Eastern Europe's first breakthrough into post-communism.